Beispiel Nr: 18
$ \text{Gegeben:} y=ax^2+bx+c \\ \text{Gesucht:} \\ \text{Scheitel und Scheitelform}\\ \text{Definitions- und Wertebereich} \\ \text{Nullstellen - Schnittpunkt mit der x-Achse} \\ \text{Faktorisiere Form} \\ \text{Scheitel} \\ Eigenschaften\\ \textbf{Gegeben:} \\ y= x^2-6x+9\\ \\ \textbf{Rechnung:} \\\bullet \text{Funktion} \\ y= x^2-6x+9\\ \\ \bullet \text{Scheitelberechnung } \\ \begin{array}{l|l} \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=1x^2-6x+9 \\ y=1(x^2-6x+9) \\ y=1(x^2-6x+3^2-3^2+9) \\ y=1[(x-3)^2-3^2+9] \\ y=1[(x-3)^2-9+9] \\ y=1[(x-3)^2+0] \\ y=1(x-3)^2+0 \\ Scheitel(3/0) \end{array} & \begin{array}{l} \text{Scheitelformel} \\ \hline y=1x^2-6x+9 \\ xs=-\frac{-6}{2\cdot 1} \\ xs=3 \\ ys=9-\frac{\left(-6\right)^2}{4\cdot1} \\ ys=0 \\ Scheitel(3/0)\\ y=1(x-3)^2+0 \end{array} \\ \end{array} \\ \\ \\\bullet\text{Definitions- und Wertebereich:}\qquad \mathbb{D} = \mathbb{R} \qquad \mathbb{W} = [0;\infty[ \\ \\\\ \\\bullet \text{Nullstellen / Schnittpunkt mit der x-Achse:} \\y= x^2-6x+9 = 0 \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ 1x^{2}-6x+9 =0 \\ x_{1/2}=\displaystyle\frac{+6 \pm\sqrt{\left(-6\right)^{2}-4\cdot 1 \cdot 9}}{2\cdot1} \\ x_{1/2}=\displaystyle \frac{+6 \pm\sqrt{0}}{2} \\ x_{1/2}=\displaystyle \frac{6 \pm0}{2} \\ x_{1}=\displaystyle \frac{6 +0}{2} \qquad x_{2}=\displaystyle \frac{6 -0}{2} \\ x_{1}=3 \qquad x_{2}=3 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ \\ x^{2}-6x+9 =0 \\ x_{1/2}=\displaystyle -\frac{-6}{2}\pm\sqrt{\left(\frac{\left(-6\right)}{2}\right)^2- 9} \\ x_{1/2}=\displaystyle 3\pm\sqrt{0} \\ x_{1/2}=\displaystyle 3\pm0 \\ x_{1}=3 \qquad x_{2}=3 \end{array}\\ \end{array}\\ \underline{x_1=3; \quad2\text{-fache Nullstelle}} \\ \\ \bullet \text{Vorzeichentabelle:} \\ \begin{array}{|c|c|c|c||} \hline & x < &3&< x\\ \hline f(x)&+&0&+\\ \hline \end{array}\\ \\ \underline{\quad x \in ]-\infty;3[\quad \cup \quad]3;\infty[\quad f(x)>0 \quad \text{oberhalb der x-Achse}}$